Regio- and diastereoselective indium-catalyzed Conia-ene reaction of ortho-alkynyl diketopiperazines to access fused diketopiperazinoindolines - Tejeneki, Hossein Zahedian; Nikbakht, Ali; Balalaie, Saeed; Rominger, Frank (The journal of organic chemistry, 2020)
An efficient synthesis of diketopiperazinoindolines through an indium-catalyzed intramolecular 5-exo-dig cyclization of ortho-alkynyl diketopiperazines has been reported. The formation of diketopiperazinoindolines proceeds via a regio- and diastereoselective Conia-ene reaction. This synthetic method opens a new door for easy access to functionalized fused diketopiperazinoindolines in high to excellent yields with exclusive Z diastereoselectivity.